DO YOUNGER AND OLDER EMPLOYEES REACT TO INTERGENERATIONAL CONFLICTS DIFFERENTLY?. (11th November 2018) - Yeung, D; Lam, W; Leung, C; Isaacowitz, D
Abstract: This paper examines whether younger and older employees differ in their emotional and behavioral reactions to conflicts occurring in the workplace. A total of 144 Chinese employees (Mage=40.2, SD=12.4; 53.5% females) took part in an experimental study conducted in the Psychology Laboratories. Four short videos depicting hypothetical workplace conflicts were presented to each participant in a randomized order. These video vignettes varied in the conflict context (intergenerational vs non-intergenerational) and intensity (high vs low). Results of Repeated Measures ANOVAs show significant age differences in emotional reactions (F=11.465, p=.001, partial η2=.077) and conflict strategies (F=3.432, p=.035, partial η2=.048). Compared with their younger peers, older employees reported less negative and more positive emotions in high-intensity conflicts. Age variations in conflict management were more likely in intergenerational conflicts than in non-intergeneration conflicts. Findings of this study reveal that conflict responses vary by the age of conflict partners and levels of conflict intensity.